KELUHAN YANG DIRASAKAN PENDERITA KANKER PAYUDARA BERDASARKAN STADIUM DAN LAMANYA KEMOTERAPI DI RSUD WALED KABUPATEN CIREBON - Retna Ayu Pengasih; Dewi Erna Marisa; Citra Setyo Dwi Andhini (Jurnal Kesehatan Mahardika, 2019)
Breast cancer is a malignancy in cells found in breast tissue that can originate from the glandular components (epithelial tracts or lobules) as well as components other than such as fat tissue, blood vessels, and nerve tissue.In Indonesia, there are two types of cancer most commonly suffered by Indonesia people, namely breast cancer and cervical cancer. There is breast cancer rate of 42,1 by 100.000 population and cervical cancer of 23,4 by 100.000 population with an average death of 13,9 by 100.000 population. In Waled Regional Public Hospital Cirebon District, from 2018, 32 breast cancer patients were obtained. This study was conducted to determine complaints in cancer patients based on the stage and duration of chemotherapy at Waled Waled Regional Public Hospital Cirebon District. This type of research is a quantitative descriptive study using a retrospective. The sampling technique used is the total sample of 32 respondents. Statistical tests were performed by univriat analysis. This research was conducted at Waled Regional Public Hospital Cirebon District. The results of this study indicate all complaints of breast cancer sufferers in Cirebon District Hospital that are less tolerable at stage IIB (100%) which supports moderate chemotherapy (100%). During chemotherapy treatment, nurses monitor patients about changes in complaints experienced by patients.